In vitro metabolism of the synthetic cannabinoid 3, 5‐AB‐CHMFUPPYCA and its 5, 3‐regioisomer and investigation of their thermal stability. Issue 2 (17th February 2016) - Franz, Florian; Angerer, Verena; Brandt, Simon D.; McLaughlin, Gavin; Kavanagh, Pierce V.; Moosmann, Bjoern; Auwärter, Volker
Abstract : Recently, the pyrazole‐containing synthetic cannabinoid N ‐(1‐amino‐3‐methyl‐1‐oxobutan‐2‐yl)‐1‐(cyclohexylmethyl)‐3‐(4‐fluorophenyl)‐1 H ‐pyrazole‐5‐carboxamide (3, 5‐AB‐CHMFUPPYCA) has been identified as a 'research chemical' both in powdered form and as an adulterant present in herbal preparations. Urine is the most common matrix used for abstinence control and the extensive metabolism of synthetic cannabinoids requires implementation of targeted analysis. The present study describes the investigation of the in vitro phase I metabolism of 3, 5‐AB‐CHMFUPPYCA and its regioisomer 5, 3‐AB‐CHMFUPPYCA using pooled human liver microsomes. Metabolic patterns of both AB‐CHMFUPPYCA isomers were qualitatively similar and dominated by oxidation of the cyclohexylmethyl side chain. Biotransformation to monohydroxylated metabolites of high abundance confirmed that these species might serve as suitable targets for urine analysis. Furthermore, since synthetic cannabinoids are commonly administered by smoking and because some metabolites can also be formed as thermolytic artefacts, the stability of both isomers was assessed under smoking conditions. Under these conditions, pyrolytic cleavage of the amide bond occurred that led to approximately 3 % conversion to heat‐induced degradation products that were also detected during metabolism. These artefactual 'metabolites' could potentially bias in vivo metabolic profiles after smoking and might have to be considered for interpretation of metabolite findings during hair analysis. This might be relevant to the analysis of hair samples where detection of metabolites is generally accepted as a strong indication of drug use rather than a potential external contamination. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The present study describes the in vitro metabolism of the synthetic cannabinoid AB‐CHMFUPPYCA and its 5, 3‐isomer. Metabolic patterns of both isomers were dominated by oxidation of the cyclohexylmethyl sidechain. Additionally, the thermal stability of both substances was assessed under smoking conditions. The terminal amide bond was pyrolytically cleaved leading to degradation products also formed by metabolic reactions. Artefactual 'metabolites' could bias in vivo metabolic profiles and should be considered for interpretation of metabolite findings, particularly in hair analysis.